2022
DOI: 10.1017/s2045796022000245
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the factorial validity and the internal reliability of the International Trauma Questionnaire (ITQ); PTSD and complex PTSD among survivors of sexual violence in Ireland

Abstract: Aims To assess the factorial validity and internal reliability of the International Trauma Questionnaire (ITQ) among a treatment-seeking sample of survivors of sexual violence in Ireland. In addition, to assess the diagnostic rate of post-traumatic stress disorder (PTSD) and complex post-traumatic stress disorder (CPTSD) among the samples. Methods Participants were adult survivors of sexual violence (N = 114) in receipt of therapeutic support at the Dublin Rape Crisis Centre. The ITQ was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Moreover, this central finding encapsulates, for the first time, a broad range of ITQ PTSD symptomatology based on ICD‐11 criteria and revealed that ITQ DSO status exerted a greater impact than ITQ PTSD status on alcohol use via anxiety. Taken together, these findings have implications for the clinical assessment and treatment of CPTSD and AUD in veterans and supports a burgeoning research literature on the mediational variables affecting these disorders in vulnerable groups (Armour et al, 2021; Frost et al, 2022; Karatzias et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, this central finding encapsulates, for the first time, a broad range of ITQ PTSD symptomatology based on ICD‐11 criteria and revealed that ITQ DSO status exerted a greater impact than ITQ PTSD status on alcohol use via anxiety. Taken together, these findings have implications for the clinical assessment and treatment of CPTSD and AUD in veterans and supports a burgeoning research literature on the mediational variables affecting these disorders in vulnerable groups (Armour et al, 2021; Frost et al, 2022; Karatzias et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…These themes are illustrated PSYCHOMETRIC ASSESSMENTS USED AS SCREENING TOOLS FOR COMPLEX POST-TRAUMATIC STRESS DISORDER (CPTSD) 68 in Tables 6, 7, 8, and 9 followed by a discussion below. First-order six-factor model Ho et al, 2019, Karatzias et al, 2016, Murphy et al, 2020, Armour et al, 2021, Frost et al, 2022 Second-order two factor model (ICD 11 CPTSD) Ho et al, 2019, Litvin et al, 2017, (Vallières et al, 2018, Karatzias et al, 2016, Haselgruber et al, 2020, Murphy et al, 2020, Gelezelyte et al, 2022, Frost et al, 2022, Sele et al, 2020, Haselgruber et al, 2019 The first prominent theme identified across the studies was which conceptual model of Most of the studies' findings demonstrated support for the second-order two-factor model of CPTSD, which is conceptually consistent with ICD-11 proposals of CPTSD as described in chapter 2. The theoretical structure of ICD-11 CPTSD was represented as the best-fitting description among participants who met the criterion for CPTSD using various measures (ITQ, CTI, ITI and ICD-TQ).…”
Section: Context and Limitations Of Reviewed Studiessupporting
confidence: 52%
“…Underreporting also remains an issue, which may have resulted in lower results in terms of prevalence. Cloitre et al, 2018, Gelezelyte et al, 2022, Haselgruber et al, 2019, Haselgruber et al, 2020, Litvin et al, 2017, Ho et al, 2019, Karatzias et al, 2016, Murphy et al, 2020, Armour et al, 2021, Frost et al, 2022, Sele et al, 2020, Vallières et al, 2018, Tian et al, 2020 Benefits and limitations of study designs Cloitre et al, 2018, Gelezelyte et al, 2022, Haselgruber et al, 2019, Haselgruber et al, 2020, Litvin et al, 2017, Ho et al, 2019, Karatzias et al, 2016, Murphy et al, 2020, Armour et al, 2021, Frost et al, 2022, Sele et al, 2020, Vallières et al, 2018, Tian et al, 2020 Reliability and validity of reviewed studies Cloitre et al, 2018, Gelezelyte et al, 2022, Haselgruber et al, 2019, Haselgruber et al, 2020, Litvin et al, 2017, Ho et al, 2019, Karatzias et al, 2016, Murphy et al, 2020, Armour et al, 2021, Frost et al, 2022, Sele et al, 2020…”
mentioning
confidence: 99%
“…Shorter instruments can measure symptoms more time-efficiently than the original test, provided that required psychometric properties are maintained (Smith et al, 2000). Previous studies of trauma-exposed clinical samples, found rates for the ITQ-12 ranging from 5.3% to 21.6% for PTSD and from 55.9% to 80.6% for CPTSD (Frost et al, 2022;Letica-Crepulja et al, 2020;Murphy et al, 2020;Vang et al, 2021), while for the ITQ-28 rates ranging from 10.9% to 25.2% for PTSD and from 36.1% to 56.3% for CPTSD have been reported (Hyland et al, 2017;Simon et al, 2019;Vallieres et al, 2018). Considering all of the above studies used a single ITQ version, a direct comparison of PTSD and CPTSD rates is not possible.…”
mentioning
confidence: 99%